PENGARUH PELATIHAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN FACTORY 3 BAGIAN CUTTING PADA PT PRATAMA ABADI INDUSTRI DI TANGERANG SELATAN - Ridhoari WP, Mellia; Andi, Dede (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the effect of job training and career development on the performance of factory employees in 3 cutting sections at PT Pratama Abadi Industri at South Tangerang either partially or simultaneously. This research method uses quantitative methods, with a sample size of 90 respondents. The data analysis techniques used are: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, simultaneous correlation coefficient test, simultaneous coefficient of determination test. simultaneous, t test and f test. Based on the t test, the value obtained is tcount > ttable (3.586>1.987) and the significance value is 0.001 <0.05. This means that job training (X1) has a significant effect on employee performance (Y). Partially testing the hypothesis for the career development variable (X2) obtained a value of tcount > ttable (4.764>1.987) and a significance value of 0.000 <0.05. This means that career development (X2) has a significant effect on employee performance (Y). Simultaneous hypothesis testing obtained a value of fcount > ftable (267.128>2.710) and a significance value of 0.000 <0.05. So it can be concluded that job training (X1) and career development (X2) have a significant simultaneous effect on employee performance (Y).